2016
DOI: 10.3171/2016.4.spine16229
|View full text |Cite
|
Sign up to set email alerts
|

Spine stereotactic radiosurgery with concurrent tyrosine kinase inhibitors for metastatic renal cell carcinoma

Abstract: OBJECT Systemic control of metastatic renal cell carcinoma (mRCC) has substantially improved with the development of VEGF, mTOR, and checkpoint inhibitors. The current first-line standard of care is a VEGF tyrosine kinase inhibitor (TKI). In preclinical models, TKIs potentiate the response to radiotherapy. Such improved efficacy may prolong the time to salvage therapies, including whole-brain radiotherapy or second-line systemic therapy. As the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 30 publications
0
17
2
Order By: Relevance
“…We did not find an association between use of TKI and improved pain response or local control in patients treated with conventional fractionated radiation. This contrasts with a recent study by Miller et al who registered improved local control in patients receiving SRS for spinal metastasis in systemic-therapy naïve patients [ 23 ]. These disparities may be accounted for by the known radiobiological differences between conventional and stereotactic radiation.…”
Section: Discussioncontrasting
confidence: 80%
“…We did not find an association between use of TKI and improved pain response or local control in patients treated with conventional fractionated radiation. This contrasts with a recent study by Miller et al who registered improved local control in patients receiving SRS for spinal metastasis in systemic-therapy naïve patients [ 23 ]. These disparities may be accounted for by the known radiobiological differences between conventional and stereotactic radiation.…”
Section: Discussioncontrasting
confidence: 80%
“…Among select patients with targetable metastatic disease, prior investigations have reported superior local control with the addition of concurrent TKIs to SRS. 28 We also observed that the addition of concurrent HER2/ EGFR TKIs to SRS significantly decreased the 12-month cumulative incidence of local failure from 15.1% to 5.7% (P < .001) (Fig. 2C), whereas the use of HER2 antibodies decreased the 12-month cumulative incidence from 18.4% to 10.2% (P 5 .003) (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…In a recentlypublished series of nearly 2000 patients undergoing SRS, renal histology, lung adenocarcinoma histology, HER2 amplification, and ALK/BRAF mutational status were associated with RN [4]. The mechanism for this effect may relate to the increased efficacy of radiation therapy when delivered with VEGFR and EGFR TKIs [20]. VEGFR TKIs alter both tumor angiogenesis and cell proliferation, simultaneously reducing vascularization of metastases while inducing cell apoptosis.…”
Section: Targeted Therapiesmentioning
confidence: 95%